RESIN MOLDING DEVICE AND METHOD OF PRODUCING RESIN MOLDED ARTICLE - MIZUMA KEITA (2019)
To provide a resin molding device capable of preventing warpage of a resin molded article from occurring.SOLUTION: A resin molding device 10 of this invention configured to perform resin molding by sealing a molding target article with thermosetting resin comprises: a molding die 111 configured of a first die (a lower die 1111) provided with a cavity and a second die (an upper die 1112) including a molding target article mounting part that mounts the molding target article; a molding die heating mechanism (a molding die heater 112) that heats the molding die 111 to a temperature within a temperature range where the thermosetting resin is set; a temperature maintaining room 13 that stores an intermediate molded article M composed of the thermosetting resin that is formed by the molding die 111 and is not yet completely set and maintains the temperature within the temperature range; and an intermediate molded article transport mechanism (a first transport mechanism 12) that transports the intermediate molded article M from the molding die 111 to the temperature maintaining room 13 while maintaining the temperature higher than a room temperature and equal to or lower than an upper limit of the temperature range.SELECTED DRAWING: Figure 1 【課題】樹脂成形品に反りが生じることを抑えることができる樹脂成形装置を提供する。【解決手段】樹脂成形装置１０は、成形対象物を熱硬化性樹脂で封止することにより樹脂成形を行う装置であって、キャビティが設けられた第１の型（下型１１１１）と、成形対象物を装着する成形対象物装着部を備える第２の型（上型１１１２）から成る成形型１１１と、成形型１１１を、前記熱硬化性樹脂が硬化する温度範囲内の温度に加熱する成形型加熱機構（成形型ヒータ１１２）と、成形型１１１で作製される、成形対象物及び完全には硬化していない前記熱硬化性樹脂から成る中間成形品Ｍを収容し、前記温度範囲内の温度に維持する温度維持室１３と、中間成形品Ｍを、室温よりも高く且つ前記温度範囲の上限以下の温度に維持しつつ成形型１１１から温度維持室１３に搬送する中間成形品搬送機構（第１搬送機構１２）とを備える。【選択図】図１